PERTIMBANGAN SELERA-BAHASA KONSUMEN DALAM PEMBUATAN IKLAN TELEVISI NASIONAL (Consideration Consumer Taste of Language in the Making of National Television Advertising) - Sriyanto Sriyanto (Balai Bahasa Sulawesi Selatan, 2015)
Effect of foreign languages that not necessary, especially English, in Indonesian language continuing and massive more so in the current global era. It can be seen in the use of foreign language in public places, such as the name of housing, hotel, restaurant, and shopping centers. It seems there is a tendency to use foreign languages like that has been captured by the advertising beings, in this case the television advertising. This study aimed to describe the influence or the use of foreign languages in advertising products on television. For that purpose, this research uses descriptive method with field data collection. Data was taken fromadvertisements broadcast by several television stations in Jakarta. The results showed that the majority of television advertising slipped foreign languages.